Gulistan hawker trade centre Gulistan, Fulbaria. Dhaka - Siddiqui, Jubayer Hasan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2021.